Analisis Bentuk Akhlak Siswa Yang Mulia Kepada Guru Dalam Prespektif Hadits - Marsya Al Farin; Royhana Safitri; Wan Elnayla Azzahra Reza; Wismanto Wismanto; Layli Sartika (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Seeking knowledge is an obligation for Muslim. In seeking knowledge, understanding and morals are needed based on religious postulates so that Allah makes it easier for the purpose of seeking knowledge. It is important for Muslims to study the arguments relating to the obligation to study and understand the morals of a student in studying in order to obtain maximum knowledge. The aim of this research is to reveal how a student should have good behavior towards the teacher according to the hadith perspective. The method used in this research is a qualitative method with a library approach, the main data sources are reading materials from books, magazines, journal articles and hadith books. The research results show that (1) students must have good intentions, straight because of Allah. Sincere intentions in his heart. The sole intention of learning is because of Allah SWT. (2) Apart from that, a student must also try to improve good morals in his efforts to study. The most important figure as a role model for students to have commendable morals is Rasulullah SAW. Rasulullah SAW is a noble creature.